Characteristics of the Flank Magnetopause: MMS Results. Issue 3 (20th March 2020) - Haaland, S.; Paschmann, G.; Øieroset, M.; Phan, T.; Hasegawa, H.; Fuselier, S. A.; Constantinescu, V.; Eriksson, S.; Trattner, K. J.; Fadanelli, S.; Tenfjord, P.; Lavraud, B.; et al.
Abstract: We have used a large number of magnetopause crossings by the Magnetospheric Multiscale (MMS) mission to investigate macroscopic properties of this current sheet, with emphasis on the flanks of the magnetopause. Macroscopic features such as thickness, location, and motion of the magnetopause were calculated as a function of local time sector. The results show that the flanks of the magnetopause are significantly thicker than the dayside magnetopause. Thicknesses vary from about 650 km near noon to over 1, 000 km near the terminator. Current densities vary in a similar manner, with average current densities around noon almost twice as high as near the terminator. We also find a dawn‐dusk asymmetry in many of the macroscopic parameters; the dawn magnetopause is thicker than at dusk, while the dusk flank is more dynamic, with a higher average normal velocity. Key Points: The magnetopause flanks are characterized using MMS observations Magnetopause flanks are thicker and have lower current density than the dayside The dawn magnetopause is marginally thicker than at dusk